RESPONSIBILITIES OF NOTARIS IN PRODUCING DEEDS MADE BASED ON FALSE INFORMATION - YOGA, SH.,MH, I GEDE PERDANA (Kerta Dyatmika, 2015)
ABSTRACTÂ In Article 1 paragraph (1) of laws No.2 of 2014 concerning the amendment to the Laws No. 30 of 2014 concerning the office of a notary states that a notary is a Public Official authorized to make an Aunthentic deed and has other authorities as set up in the legislation or under other laws. Deed made before a notary can be classified in two (2) kinds of certificates, namely partij deed/deed of the parties and the deed of relaas/officials. The problem discussed in this thesis is what is the legal regulation of the production of notarial deed in the legislation in Indonesia, what is the legal effect of a deed made based on false information by the parties involved.The conclusion of the study demonstrates that notaris in running his or her office must pay attention to and must be subject to the Laws No. 30 of 2004 concerning the post of a notary which has been amended by the enactment of Laws No 2 of 2014 concerning the amendment to the Laws No 30 of 2004 concerning the office of a notary and ethical codes for a notary which constitutes applicable regulations for moral guidance for a notary profession. A deed that contains false information which is provided by the parties can be cancelled. Deed cancellation can be done by a notary if demanded by the parties who suffer losses.Â Keywords : Responsibility, Notaris, Deeds, False Information.Â